One-step electrochemical deposition of PolypyrroleChitosanIron oxide nanocomposite films for non-enzymatic glucose biosensor - AL-Mokaram, Ali M.A. Abdul Amir; Yahya, Rosiyah; Abdi, Mahnaz M.; Ekramul Mahmud, Habibun Nabi Muhammad (Elsevier, 2016)
One-step electrodeposition method of Polypyrrole–Chitosan–Iron oxide (Ppy–CS–Fe3O4) nanocomposite films (Ppy–CS–Fe3O4NP/ITO) has been developed for the fabrication of advanced composite coatings for biosensors applications. The FESEM and EDX results provide the evidence of successful incorporation of Fe3O4 into Ppy–CS molecules. The presence of Fe3O4 nanoparticles in the nanocomposite films was further confirmed by the XRD and XPS spectrums. The fabricated electrode Ppy–CS–Fe3O4 NP/ITO shows a fast amperometric response with high selectivity to detect glucose non-enzymatically with improved linearity (1–16 mM) and the detection limit of (234 μM) at a signal-to-noise ratio (S/N=3.0).